Developing a production management model for multi-project based small and medium sized manufacturing companies - Somel, Hasan Emrah (My University, 2003)
Ülkemizde inşaat sektörüyle bağlantılı bir çok imalat sektörü standart üretim yapabilme olanaklarına sahip değildir çünkü ülkemizdeki inşaatların standart olmayan yapıları vardır. Bu nedenle seri üretimden proje bazlı tekil üretime yönelen firmalar, proje yönetiminde problemler yaşamaktadırlar. Bu çalışma kapsamında aynı anda birden çok proje sürdürmek durumunda kalan bu tip işletmeler için, organizasyonel yapı, dökümantasyon, bilgisayarlı proje yönetimi, optimum üretim programları oluşturulması ve entegre performans değerlendirme sistemleri üzerinde geliştirme çalışmaları yapılmıştır. Organizasyonel yapı, dökümantasyon ve bilgisayarlı proje yönetimi konularında mevcut sistemler incelenmiş ve uygun sistemlerin örnek bir şirket üzerinde uygulaması yapılmıştır. Optimum üretim programları oluşturulması için mevcut bilimsel literatür incelenmiş ve uygun bulunan bir sistem daha önce seçilen bilgisayar entegre edilerek uygulanmıştır. Performans değerlendirme sistemi için de örnek şirket proje müdürlerinin de fikirleri alınarak, seçili proje yönetimi yazılımı altında çalışan bir performans değerlendirme sistemi geliştirilmiştir. Yapılan bu çalışmaların benzer şartlardaki aynı veya farklı sektörlerden birçok işletmeye uygulanabileceği görülmüştür. Kasım, 2003 Hasan Emrah Somel In Turkey many sectors related to the building construction sector has not got the ability to manufacture standart products because of the nonstandardized structures of building constructions. The companies are directed from mass production systems to project based production systems and they have some problems in project management. In this study the organizational structure, documentation, computerized project management, optimum scheduling of resource constrained multi-projects and integrated performance evaluation system development studies has been performed for such companies having multiple project manufacturing systems. The existing systems have been examined for organizational structure, documentation, and computerized project management development, and the application of the appropriate systems on a selected company has been done. For the problem of optimum scheduling of multi-project systems, the technical literature has been surveyed and an appropriate heuristic system has been applied by entegrating with the selected project management software. A performance evaluation system has been developed by also taking the opinions of the project managers in the company. The system has been adapted to work under the selected project management software. It is observed that this study can be applied to many similar companies both in the same sector or other related sectors.
Keywords: Genel yönetim; Küçük İşletmeler; Üretim yönetimi; Yönetim